1977
DOI: 10.1017/s0022149x00007677
|View full text |Cite
|
Sign up to set email alerts
|

The response of nematodes in vivo and in vitro to some anthelmintics

Abstract: Dietary feeding of drugs for 5 days to mice infected with Nematospiroides dubius and Hymenolepis nana detected all modern anthelmintics examined except stilbazium. A simple test using eggs of Nematodirus spathiger and adult Nippostrongylus brasiliensis to detect anthelmintics in vitro is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1981
1981
1989
1989

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Albendazole is active in vitro against C. elegans at 0-5 ng/ml (SIMPKIN & COLES, 1981) and in vivo against Nematospiroides dubius at 125 p.p.m. (COLES & MCNEILLIE, 1977) but no activity was found with triclabendazole at higher doses against these nematodes. For the optimal response of C. elegans to several anthelmintics particulate matter should be present in the medium (unpublished) so precipitated triclabendazole should not have interfered with the test.…”
Section: Discussionmentioning
confidence: 88%
“…Albendazole is active in vitro against C. elegans at 0-5 ng/ml (SIMPKIN & COLES, 1981) and in vivo against Nematospiroides dubius at 125 p.p.m. (COLES & MCNEILLIE, 1977) but no activity was found with triclabendazole at higher doses against these nematodes. For the optimal response of C. elegans to several anthelmintics particulate matter should be present in the medium (unpublished) so precipitated triclabendazole should not have interfered with the test.…”
Section: Discussionmentioning
confidence: 88%
“…It is worth noting that some other trichostrongylid worms not employed in the Present work, namely those of the genus Nematodints, would probably be unsuitable f°r such screens. COLES & MCNEILLIE (1977) showed that the eggs and developing larvae of N. spathiger were insensitive to compounds such as the imidazothiazoles and Pyrimidines. We suggest that this phenomenon may have been associated with the fact t n at unlike most trichostrongyles, the first, second and early third-stage larvae of Parasites of this genus are contained within the egg, which may be an impenetrable barrier to these particular compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Θεωρητικά, παρόλο που η δοκιμή αυτή προσφέρεται για όλες τις ομάδες των ανθελμινθικών φαρμάκων, έχει χρησιμοποιηθεί μόνο για λίγα από τα παράσιτα που παρουσιάζουν ενδιαφέρον. Αυτό συμβαίνει επειδή είναι περισσότερο δαπανηρή και χρονοβόρα από τις αντίστοιχες in vitro δοκιμές, εφαρμόζεται αποκλειστικά στο εργαστήριο και απαιτεί τη χρησιμοποίηση πειραματόζωων (Coles and McNeillie, 1977). Επιπρόσθετα, υπάρχουν δυσκολίες στην αξιολόγηση ανθελμινθικών φαρμάκων που για να δράσουν απαιτείται η διάσπαση τους μέσα στον ξενιστή, ιδιαίτερα στις περιπτώσεις που η διάσπαση τους μέσα στο τρωκτικό είναι διαφορετική από εκείνη στα πολυγαστρικά ζώα, για τα οποία προορίζεται το φάρμακο (Jenkins ei al., 1980).…”
Section: ) δοκιμές με χρήση πειραματόζωων (τρωκτικών)unclassified